Portuguese language as a distinguishing mark: an East Timorese identity school during the Indonesian occupation (Educação e Pesquisa, 2021)
East Timorese fought for 24 years (1975-1999) against the violent Indonesian occupation and the educational effort to make them Indonesians. This research consists of a case study intended to understand the purpose of a school named Externato de São José in maintaining all teaching in the Portuguese language when it was banned and persecuted for delaying effective integration in Indonesia during that period. A qualitative methodology is used under the interpretive paradigm. In order to better understand this school’s objectives, it was decided to listen to its privileged witnesses, carrying out a content analysis of ten semi-structured interviews with former students, teachers, and members of society. The research undertaken reinforces the idea that identity is seductive, that it depends on people’s free adhesion, and projects a sense of belonging to something bigger, to a people with a unique culture, with language, in conjunction with other cultural features, playing a decisive role. Results show 124 occurrences illustrating the school’s aim in promoting the Portuguese language as a distinguishing hallmark of East Timorese cultural identity, being highlighted by the interviewees as the essence of their identity, as a rejection of Indonesian language and cultural integration in Indonesia, or as a recovery of East Timor culture, of Portuguese/Latin influence. This central identity role given to the Portuguese language, either by pro-integration in Indonesia and pro-independence supporters, unified the older generation educated in Portuguese and part of the youth in the struggle for independence, thus contradicting any lasting uncertainties in East Timor society regarding the status of Portuguese as one of the two official languages.